Geological Structure Analysis of Satellit Gravity Data in Oil and Gas Prospect Area of West Aceh-Indonesia - Dian Darisma; Marwan Marwan; Nazli Ismail (PSI-Aceh, 2019)
Estimation of the subsurface geological structures in oil and gas prospect area of West Aceh has been done by utilizing gravity field anomaly of satellite gravity data. This research aim to analyze satellite gravity data in order to get geological features which is include deep and shallow structure or fault around oil and gas prospect area in West Aceh. The satellite gravity data is originally provided as Free Air Anomaly and should be corrected to get Complete Bouguer Anomaly (CBA). Furthermore, CBA was transformed into a horizontal plane and corrected from regional anomalous effects to obtain residual anomaly, horizontal and vertical derivative. From CBA, the gravity anomaly show good correlation with geological boundaries on different rock formation and the anomaly is decrease from NE-SW. Residual anomaly also gives same information with CBA but this anomaly focus on shallow structure. Furthermore, horizontal derivative and vertical derivative also show good correlation with geological structure or fault but in some areas the anomaly related with deep structure cannot be seen on the surface or geological map. Despite the result cannot correlate directly with oil and gas prospect area, satellite gravity can be used to identify gravity anomaly and also fault that related with hydrocarbon anomaly area